Seed generation effect on quality of genetic information from maize (Zea mays L.) diallel cross for maize weevil (Sitophilus zeamais Motschulsky) resistance - Kasozi, L.C.; Derera, J.; Tongoona, Pangirayi; Gasura, E. (Springer, 2021)
Maize weevil (Sitophilus zeamais Motschulsky) is a common insect pest affecting stored maize (Zea mays L.) worldwide and can be controlled by breeding for host resistance. Information on combining ability and gene effects conditioning maize weevil resistance would be required to devise breeding strategies. However, there are disagreements regarding the seed generation to subject to maize weevil resistance evaluation. This study determined the seed generation effect on the quality of genetic information obtained from a maize diallel cross. Eight weevil-resistant and two susceptible maize inbred lines from eastern and southern Africa were crossed in a 10-parent diallel scheme. The resulting F1 hybrid seed, F2 full-sib grain from controlled pollination, and F2 half-sib grain from open pollination were evaluated for maize weevil resistance and responses were determined using the number of F1 weevil emergence from the seed (FWE), median development period (MDP), Dobie’s index of susceptibility (DIS), and parental weevil mortality (PWM). General combining ability (GCA) and specific combining ability (SCA) effects were significant for the FWE, MDP, and DIS in all seed categories. Results revealed that reciprocal effects were predominant in F1 hybrid seed, GCA effects were predominant in F2 full-sib grain, while SCA effects were more important in the F2 half-sib grain. The F2 full-sib generation exhibited superiority in providing genetic information required for parental line selection when breeding for weevil resistance, compared to F1 hybrid and F2 half-sib grain. Resistant inbred lines MV170 and MV142, produced hybrids that exhibited high levels of maize weevil resistance across all the three seed categories thus, qualifying as suitable materials for breeding weevil resistant maize hybrids.